Environmental Pollution and Damage Control Through Management of Licensing at the Regional Level - yadi, Mul; Siregar, Fahrul; Hasyim, Inayatullah Abd. (Fakultas Hukum Universitas Djuanda Bogor, 2018)
The objectives to be desired in this study are to analyze and assess control to pollution and environmental damage through management of permits in Bogor Regency, and explain administrative claims for business licenses and/or activities that have already been revoked, if the business already has a business license and/or activity is not in accordance with Article 121 of the Environmental Protection and Management Law. One of the instruments in an effort to prevent pollution and environmental destruction is environmental permits, as stipulated in Article 1 point 35 of Law No. 32 of 2009 which is then regulated in Government Regulation No. 27 of 2012 concerning Environmental Permits. In this provision there are two types of permits, namely environmental permits. The research method used is an empirical normative juridical research method with the consideration that the starting point of the research is analysis of legislation governing licensing. The results of this study illustrate that environmental permits are one of the instruments in efforts to prevent pollution or damage to the environment, to realize the goals of environmental protection and management, especially in the use of the environment associated with environmental permits. Implementation and enforcement of permits will affect the pollution and damage to the existing environment. Therefore local governments are required to enforce environmental law in implementing policies or licensing related to the environment, even if various efforts need to be made, including revocation of licenses and use of criminal channels for those who do not heed destruction and pollution.